PENERAPAN MODEL COOPERATIVE LEARNING TIPE SNOWBALL THROWING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPS SISWA SD - Zulfiati, Heri Maria (Profesi Pendidikan Dasar, 2014)
This classroom action research aims to determine the increase in activity and resultsactivity with cooperative learning model snowball throwing on learning social studiesclass IV students second semester Elementary School District 1 Rejowinangun schoolYogyakarta year 2013/2014. This study was conducted in two cycles, the subjects inthis study were as many as 28 people and the object of research is the result of learningactivity social studies. Student activity data were collected using the method of observation,while the results of the data gathered through the sosial studies test methodwhich tests learning outcomes. The results show the application of Cooperative LearningModel Type Snowball Throwing in learning social studies can increase activity andlearning Outcomes. Increased activity of students in the first cycle 63.40 % and 81.91% in the second cycle or in other words an increase of 18.51 % active students areincluded in the active category. Student learning outcomes in the first cycle 72.84% and83.26% in the second cycle. There has been an increase in science learning outcomes of18.00 % included in the high category. Based on these data the application of cooperativelearning model Snowball Throwing concluded that learning can enhance the activitysocial studies student learning outcomes.